ONLINE NUCLEAR ORIENTATION AND RELAXATION STUDIES OF CS ISOTOPES - Shaw, T; Green, V; Ashworth, C; Rikovska, J; Stone, N; Walker, P; Grant, I (Kluwer Academic Publishers, 1987)
The hyperfine field of Cs Fe has been measured to be (+)40.8(0.7)T, using the technique of on-line low temperature nuclear orientation. The time dependent relaxation of121CsmFe has also been investigated using a new technique, giving a Korringa constant Ck of 0.059 (15) sK. From this, an effective relaxation time of 3.0 (0.8)s can be deduced for the short lived118Csm(T1/2=17s). This value has then been used to extract the magnetic moment of118Csm to be |μ|=5.4 (1.1) nm. © 1987 J.C. Baltzer A.G., Scientific Publishing Company.